2020
DOI: 10.1111/eea.12890
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic and additive interactions among components of food‐based baits underlie female fruit fly attraction

Abstract: Attraction of tephritid fruit flies to some food sources can be enhanced by the presence of ammonia derivatives, compounds that are perceived as volatile cues for protein-rich food sources. Using a comparative approach, we (1) evaluated the behavioral responses of females of three invasive fruit fly species, Bactrocera (Zeugodacus) cucurbitae (Coquillett), Bactrocera dorsalis (Hendel), and Ceratitis capitata (Wiedemann) (all Diptera: Tephritidae) to trub (a protein-rich waste brewer's yeast product generated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
2
18
0
1
Order By: Relevance
“…Although ammonia seems to be a key attraction component, our results agree with previous studies in which ammonia alone did not fully account for the attraction of flies [9,15,16,21,28,29]. This was corroborated in our experiments, in which the capture of flies was significantly improved when torula yeast was added to 150 mM ammonia solution ( Table 2).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although ammonia seems to be a key attraction component, our results agree with previous studies in which ammonia alone did not fully account for the attraction of flies [9,15,16,21,28,29]. This was corroborated in our experiments, in which the capture of flies was significantly improved when torula yeast was added to 150 mM ammonia solution ( Table 2).…”
Section: Discussionsupporting
confidence: 93%
“…Ammonia is considered one of the most important components that modulate tephritid responses to food-based attractants [ 9 , 10 , 15 , 17 ]. Tephritid species vary in their responses to sources of ammonia, which appear to be capable of both additive and synergistic effects if other food-based substances are present, such as grape juice or protein-rich waste from the brewing industry at different stages of decomposition [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study to evaluate the incorporation of ammonium acetate into protein-borax mixtures used in monitoring traps. Although attraction appears to vary across species, these findings reinforce previous observations that have indicated that the amount of ammonia released by food-based substances is less influential on the attraction of tephritid flies when other protein-derived odors are also present ( Piñero et al 2020 ; Lasa and Williams 2021 ). Additional studies on protein-derived semiochemicals and their interaction with ammonia could lead to improved attractants for trap-based monitoring of tephritid pests.…”
Section: Discussionsupporting
confidence: 87%
“…The attraction of Ceratitis, Bactrocera, and Zeugodacus species to proteinaceous and non-proteinaceous substances was studied by Piñero et al (2020) , with and without the addition of ammonium acetate. These authors observed that ammonia tended to be less attractive to tephritids when protein-derived odors were also present.…”
Section: Discussionmentioning
confidence: 99%